(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background : Different studies had been carried out at different hospitals through- out the world to find out incidence and to assess the risk factor of ETT and TT blockage at ICU setup. The aim of our study was to reach a consensus and to find out the best diagnostic tool to assess the incidence and associated risk factors ETT and TT blockage at ICU setup. To assess the incidence and associated risk factors ETT and TT blockage at ICU setup. Materials and methods : Endotracheal Tube (ETT) and Tracheostomy Tube (TT) blockage is a common phenomenon at the Intensive Care Unit (ICU) setup of hospital . This is a cross sectional study carried out in the Medical Centre Hospital Between July 2018 to June 2019. Total 60 patients were included in the study. Data were analyzed and presented as both qualitative and quantitative data as applicable using SPSS version 20.The quantitative data were analyzed by mean, standard deviation. The qualitative data were analyzed by Mc NEMAR test (Mc NEMAR X2 test). For all analytical test, the level of significance was set at 0.05 and p value equal or less then 0.05 was considered as significant, p value more than 0.05 was considered as not significant. Results : A total 60 patients were included in the study, who required mechanical ventilation support for different purposes either though ETT and/or TT. The Incidence of ETT/TT blockage was 9(15%). From those ETT was 6(10%) and TT was 3(05%) (p=0.042). Most causes of tube blockage was mucus 5(55.56%), debris 3(33.33%) and kinking of the tube 1(11.11%). The incidence of partial blockage was 5(55.56%) and complete blockage was 4(44.44%) consecutively (P=0.025). so it is statistically significant. During the night shift tube blockage was 6(66.67%) was slightly higher than the day shift, which was 3(33.33%). Conclusion : ETT and/or TT blockage is an expected outcome in ICU setup . In spite of all measures, keen observation is very important to find out the blockage problem for early intervention. JCMCTA 2021 ; 32 (2) : 132-136